Germinação e aspectos morfológicos de sementes de Archontophoenix cunninghamii H. Wendl. & Drude (Arecaceae) - Luz, Petterson Baptista da [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
The Australian real palm (Archontophoenix cunninghamii H. Wendl. & Drude) has a major use in landscaping. Among producers because of its possibility as an alternative for the production of palm heart, which leads to an increase in the demand for its seedlings. This palm tree is of great ornamental and commercial interest, there are still many unknown aspects related to seedling production. There is no scientific information about the germination tests such as temperature, germination medium, seedling morphology or the seed behavior during storage. For the study of temperature effect, six temperatures regimes (20ºC, 25ºC, 30ºC, 35ºC, 20-30ºC and 25- 35ºC) were evaluated, using vermiculite as the germination medium. A completely randomized design with four replicates of 25 seeds each was adopted. Three germination media were analyzed (sand, vermiculite and sphagnum) at an alternate temperature of 25-35ºC. For the study of the germination medium, the design adopted was the completely randomized design with seven replicates of 25 seeds each. For the study of the effect of soaking of the seeds, a seedlot containing approximately 1000 seeds was kept in distilled water. Each day, a sample containing 100 seeds was set to germinate. The maximum period of soaking was of seven days, which means that the experiment had eight treatments: sowing right after the harvesting and from day 1 to day 7 after the harvesting, where four replicates of 25 seeds were used for each day. For the storage study, the experimental design used was the completely randomized design (12 periods of storage) with four repetitions of 25 seeds. The seeds were placed in impermeable packages (bags of transparent polyethylene) and were stored in a refrigerated chamber. The storage lasted for 11 months and at every 30 days, samples containing 140 seeds were taken out. From these 140 seeds, 100 were taken... (Complete abstract click electronic access below)

A palmeira real australiana (Archontophoenix cunninghamii H. Wendl. & Drude) é uma das palmeiras exóticas de maior utilização no paisagismo e nos últimos tempos tem despertado grande interesse também no cultivo para a produção de palmito, aumentando a procura por mudas. Embora seja uma palmeira de grande interesse ornamental e comercial, ainda pairam muitas dúvidas relacionadas à produção de mudas. Não há informações científicas sobre os padrões de teste de germinação, como temperatura, substrato, morfologia do diásporo e das plântulas e o comportamento das sementes submetidas ao armazenamento. Desta forma o objetivo deste trabalho foi estudar a germinação de sementes, bem como, a morfologia do diásporo (semente com o endocarpo aderido) e da plântula de A. cunninghamii. Para estudo do efeito da temperatura, foram avaliadas seis regimes de temperaturas (20ºC, 25ºC, 30ºC, 35ºC, 20-30ºC e 25-35ºC), utilizando como substrato vermiculita; o delineamento adotado foi inteiramente casualizado, com 4 repetições de 25 sementes. Para o estudo dos substratos, foram avaliados três substratos (areia, vermiculita e esfagno), na temperatura alternada de 25-35ºC; o delineamento adotado foi o inteiramente casualizado, com 7 repetições de 25 sementes. Para o estudo do efeito da embebição das sementes aproximadamente 1000 sementes foram colocadas para embeber em água destilada, a cada 1 dia uma amostra de 100 sementes era colocada para germinar, onde o período máximo de embebição foi de 7 dias. O experimento contou com 8 tratamentos: semeadura logo após a colheita e de 1 a 7 dias após onde foi utilizado 4 repetições de 25 sementes cada. Para o estudo do armazenamento o delineamento experimental utilizado foi o inteiramente casualizado; com 12 tratamentos (semeadura logo após a colheita e a cada 30 dias durante 11 meses) e 4 repetições de 25 sementes...
Keywords: Palmeira; Sementes - Armazenamento; Seed storage; Palm; Seed